Kinetic Study of the Interaction Between Some Thiacrown Ethers and Iodine Monobromide - JAVADIAN JAZI, MAHMOUD; REZA FIROOZ, ALI; SEMNANI, ABOLFAZL (Asian Journal of Chemistry, 2010)
A spectrophotometric study concerning the interaction between trithia-9-crown-3(TT9C3), tetrathia-12-crown-4 (TT12C4) and hexathia-18-crown-6 (HT18C6) as n-donors with iodine monobromide as s-acceptor has been followed spectrophotometrically in dichloromethane and trichloromethane solution at 25 ºC. The results are indicative of the formation charge transfer complex in first step followed by the conversion of charge transfer to ionic complex. The rate constants of conversions are obtained from the plot of ln (At/A0) vs. t and vary in the order: TT9C3 > TT12C4 > HT18C6. Moreover, the results show the faster reactions in dichloromethane than that of trichloromethane. The possible reasons for such observations are discussed. The conductivity measurements indicate that the free ions are not formed.